Implementasi Peraturan Daerah Kabupaten Kampar Nomor 14 Tahun 2017 Tentang Pegelolaan Barang Milik Daerah Pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Kampar - Bella Monisa; Dadang Mashur (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
State assets are economic resources that are used optimally. In addition to being able to provide Non-Tax State Revenue (PNBP) to the state, the assets used will be maintained so that maintenance costs can be saved. Therefore, Kampar Regency issued Kampar Regency Regional Regulation Number 14 of 2017 concerning management of regional property so that it optimizes managing property. area, especially in terms of administration. However, many vehicle assets were found in damaged condition in each regional apparatus organization of Kampar Regency. These unproductive assets will eventually cause new problems, because assets will lose their productive value and have an impact on economic potential and will increasingly burden the Kampar area's finances. This study uses the theory of George C. Edwards which uses 4 indicators, namely communication, human resources, disposition and bureaucratic structure. The research method is qualitative using data collection techniques by observation, interviews and documentation to the informants involved through a purposive sampling technique. The results of this study found that the management of regional property was not optimal as evidenced by the weak administration and administrative inventory of documents both manually and by using the asset module SIPKD website application. Furthermore, superior and quality human resources have not been optimal.